Tratamiento contable de los ingresos procedentes de contratos y la utilidad neta en agencias navieras - Vilema Cedeño, Yadira Nathaly (2022)
The present investigation consists of the Accounting Treatment of Income from Contracts in Shipping Sector Agencies, with the implementation of a Manual of Policies and Procedures, which will contribute to accounting management, promoting reasonableness in the presentation of Financial Statements, which show the economic and financial health of the Shipping Agencies, which contributes to decision making. In Chapter 1, details the approach to the problem, formulation of the problem, systematization, delimitation, general and specific objectives, justification, idea to defend and variables...........